SQL Server 2005 T-SQL Recipes: A Problem-Solution Approach - Sack, Sack (Apress, 2013)
When it comes to performing your daily SQL Server tasks, technical documentation tends to tell you more than you need to know. Let’s say that you’re in a hurry, and you want to add a unique constraint to a table before someone inserts a duplicate value into it. Where do you look? One obvious choice is SQL Server Books Online. With its massive amounts of useful information, you know that the answer has to be there somewhere. Unfortunately, finding this information may involve several click-throughs and red herrings. Once you do arrive at the correct page, the information you need may be integrated into a larger syntax block, with unrelated functionality or examples. SQL Server 2005 T-SQL Recipes was written in order to address the need for fast information retrieval and use. Topics are presented in a task-based format. Each topic (recipe) provides the necessary background to get you started, presents one or more examples, and then concisely explains how it all works. Whether you need to brush up on a topic you haven’t used for a while, or whether you’re new to Transact-SQL, you can easily pick and choose the areas you need to work on. This book covers the basics and beyond, demonstrating the more complex techniques and functionality offered in SQL Server 2005’s flavor of Transact-SQL. Want to learn more about what’s new in SQL Server 2005? This book will also demonstrate the new Transact-SQL features and functionality introduced in SQL Server 2005, allowing you to quickly test out features with aminimal amount of fuss. Written to be index-friendly, the book does not need to be read front to back in order for readers to benefit from it. Whether you are a novice, part-time, or seasoned SQL Server professional, SQL Server 2005 T-SQL Recipes will provide you with the fast facts needed to help you get the job done.